Dihydromyricetin Acts as a Potential Redox Balance Mediator in Cancer Chemoprevention - Liang Chen; Meng Shi; Chenghao Lv; Ying Song; Yuanjie Wu; Suifei Liu; Zhibing Zheng; Xiangyang Lu; Si Qin (Mediators of Inflammation)
Dihydromyricetin (DHM) is a flavonoid extracted from the leaves and stems of the edible plant Ampelopsis grossedentata that has been used for Chinese Traditional Medicine. It has attracted considerable attention from consumers due to its beneficial properties including anticancer, antioxidative, and anti-inflammatory activities. Continuous oxidative stress caused by intracellular redox imbalance can lead to chronic inflammation, which is intimately associated with the initiation, promotion, and progression of cancer. DHM is considered a potential redox regulator for chronic disease prevention, and its biological activities are abundantly evaluated by using diverse cell and animal models. However, clinical investigations are still scanty. This review summarizes the current potential chemopreventive effects of DHM, including its properties such as anticancer, antioxidative, and anti-inflammatory activities, and further discusses the underlying molecular mechanisms of DHM in cancer chemoprevention by targeting redox balance and influencing the gut microbiota.